Mihita La Ua Uatto as a Normative Moral Order: Converging Customary Law and Islamic Penal Law - Islamul Haq; Rasna Rasna; Resi Resi; Habib Maulana Maslahul Adi; Agam Royana (De Jure: Jurnal Hukum dan Syari'ah, 2026)
This study examines the philosophy, social function, and contemporary implementation of the Iha customary caning law known as Mihita La Ua Uatto, which is grounded in the local philosophical adage, “where there is balance, there is peace.” The research seeks to: (1) analyse the role of this customary sanction in preserving social and spiritual order within the Iha community amid contemporary legal and social transformation; and (2) explore the convergence between its restorative values and the foundational principles of Islamic Penal Law (Hukum Pidana Islam), particularly al-Ta’dīb (moral education) and al-‘Adālah (justice). This study employs a qualitative socio-legal approach through field interviews with customary leaders, religious figures, and community members, supported by an examination of customary records, local narratives, and relevant legal literature. The findings reveal that Mihita La Ua Uatto derives its authority not merely from coercive punishment, but from collective moral legitimacy, ritual symbolism, and communal participation that reinforce social harmony and accountability. The study further formulates the concept of al-ʿUqūbah al-Jamāʿiyyah al-Mutakāmilah (Integrated Collective Punishment Theory), which emphasises that sanctions become socially effective when embedded within collective ethical consciousness and restorative objectives. This research demonstrates that customary law operates as a living normative order capable of contributing to the harmonisation of local wisdom, Islamic legal values, and national legal development. Keywords: customary law; mihita la ua uatto; Islamic law.